Revealing the role of organic cations in hybrid halide perovskite CH3NH3PbI3 - Carlo Motta (2884388) (2015)
The hybrid halide perovskite CH3NH3PbI3 has enabled solar cells to reach an efficiency of about 20%, demonstrating a pace for improvements with no precedents in the solar energy arena. Despite such explosive progress, the microscopic origin behind the success of such material is still debated, with the role played by the organic cations in the light-harvesting process remaining unclear. Here van der Waals-corrected density functional theory calculations reveal that the orientation of the organic molecules plays a fundamental role in determining the material electronic properties. For instance, if CH3NH3 orients along a (011)-like direction, the PbI6 octahedral cage will distort and the bandgap will become indirect. Our results suggest that molecular rotations, with the consequent dynamical change of the band structure, might be at the origin of the slow carrier recombination and the superior conversion efficiency of CH3NH3PbI3 . Other Information Published in: Nature Communications License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1038/ncomms8026